Genital interactions during simulated copulation among marine mammals. Issue 1864 (11th October 2017) - Orbach, Dara N.; Kelly, Diane A.; Solano, Mauricio; Brennan, Patricia L. R.
Abstract : Genitalia are morphologically variable across many taxa and in physical contact during intromission, but little is known about how variation in form correlates with function during copulation. Marine mammals offer important insights into the evolutionary forces that act on genital morphology because they have diverse genitalia and are adapted to aquatic living and mating. Cetaceans have a fibroelastic penis and muscular vaginal folds, while pinnipeds have a baculum and lack vaginal folds. We examined copulatory fit in naturally deceased marine mammals to identify anatomical landmarks in contact during copulation and the potential depth of penile penetration into the vagina. Excised penises were artificially inflated to erection with pressurized saline and compared with silicone vaginal endocasts and within excised vaginas in simulated copulation using high-resolution, diffusible iodine-based, contrast-enhanced computed tomography. We found evidence suggestive of both congruent and antagonistic genital coevolution, depending on the species. We suggest that sexual selection influences morphological shape. This study improves our understanding of how mechanical interactions during copulation influence the shape of genitalia and affect fertility, and has broad applications to other taxa and species conservation.